The role of nurses and midwives in the provision of abortion care: A scoping review. Issue 9 (29th February 2020) - Mainey, Lydia; O'Mullan, Catherine; Reid‐Searl, Kerry; Taylor, Annabel; Baird, Kathleen
Abstract: Aims and objectives: To define the role and scope of the nurse and midwife within the global context of abortion. Background: An estimated 56 million women seek abortions each year; nurses and midwives are commonly involved in their care (Singh et al., 2018, https://www.guttmacher.org/sites/default/files/report_pdf/abortion-worldwide-2017.pdf ). As new models of abortion care emerge, there is a pressing need to develop a baseline understanding of the role and scope of nurses and midwives who care for women seeking abortions. Design: The review design was Arksey and O'Malley's five‐stage methodological framework. The review follows the PRISMA‐ScR checklist. Methods: MEDLINE, CINAHL, Scopus and ScienceDirect were used to identify original research, commentaries and reports, published between 2008–2019, from which we selected 74 publications reporting on the nursing or midwifery role in abortion care. Results: Nurses and midwives provide abortion care in a variety of practice. Three themes emerged from the literature: the regulated role; providing psychosocial care; and the expanding scope of practice. Conclusions: The literature on nursing and midwifery practice in abortion care is broad. Abortion‐related practices are potentially over‐regulated. Appropriately trained nurses and midwives can provide abortions as safely as physicians. The preparation of nurses and midwives to provide abortion care requires further research. Also, healthcare organisations should explore person‐centred models of abortion care. Relevance to clinical practice: Abortion care is a common procedure performed across many healthcare settings. Nurses and midwives provide technical and psychosocial care to women who seek abortions. Governments and regulatory bodies could safely extend their scope of practice to increase women's access to safe abortions. Introduction of education programmes, as well as embedding practice in person‐centred models of care, may improve outcomes for women seeking abortions.